Epigenetic analysis in a murine genetic model of Gulf War illness - Mozhui, Khyobeni; O’Callaghan, James P.; Ashbrook, David G.; Prins, Pjotr; Zhao, Wenyuan; Lu, Lu; Jones, Byron C. (Frontiers in Toxicology, 2023)
Of the nearly 1 million military personnel who participated in the 1990-1991 Gulf War, between 25% and 35% became ill with what now is referred to as Gulf War Illness (GWI), by the Department of Defense. Symptoms varied from gastrointestinal distress to lethargy, memory loss, inability to concentrate, depression, respiratory and reproductive problems. The symptoms have persisted for 30 years in those afflicted but the basis of the illness remains largely unknown. Nerve agents and other chemical exposures in theater have been implicated but the long-term effects of these acute exposures have left few if any identifiable signatures. The major aim of this study is to elucidate the possible genomic basis for the persistence of symptoms, especially of the neurological and behavioral effects. To address this, we performed a whole genome epigenetic analysis of the proposed cause of GWI, viz., exposure to organophosphate neurotoxicants combined with high circulating glucocorticoids in two inbred mouse strains, C57BL/6J and DBA/2J. The animals received corticosterone in their drinking water (20mg%, w/v) for 7 days followed by injection of diisopropylfluorophosphate, a nerve agent surrogate (DFP, 4mg/kg, i.p.). Control mice were maintained under normal husbandry. Six weeks after DFP injection, the animals were euthanized and medial prefrontal cortex harvested for genomic methylation analysis by MBD-seq. We observed 67 differentially methylated genes, notably among them, Ttll7, Akr1c14, Slc44a4, and Rusc2, all related to different symptoms of GWI. Our results support proof of principle of genetic differences in the chronic effects of GWI-related exposures and may reveal why the disease has persisted in many of the now aging Gulf War veterans.